Neutral Zone: A Concept and Technique Application for Managing Severely Resorbed - Fitri, Ainy; Agustono, Bambang (Indonesia Prosthodontic Association, 2021)
Background: Full dental prosthesis rehabilitation on flat mandibular ridge has been a difficult case for clinician for a long time. A huge resorption of mandibular ridge resulted in not enough retention, tounge muscle force as well as lips and cheek muscle causing a decrease in denture’s stability and retention. Neutral zone is a potential area or position where lips and cheek on one side, and tounge on the other side have balance pressure. Purpose: To acquire optimum stability of the denture, arrangement of the mandibular teeth in full dental prosthesis must follow the neutral zone. Case Report: A 60-year-old male patient with a chief complaint of difficulty in mastication, loosening of upper and lower dentures, he also complained of denture moving during swallowing and speaking. Case Management: Preliminary impression was done using alginate. Then, horizontal and vertical jaw relation was recorded using bite rim. Suction method impression technique was used to acquire functional impression. Lower denture teeth arrangement followed the result of neutral zone impression. Acrylic denture was being contoured to follow natural anatomy of the oral cavity. Conclusion: The result of the treatment is patient get full denture with maximum retention and stability while speaking as well as masticating. This article explains about the making of full dental prosthesis with pressure point on neutral zone impression technique on flat mandibular ridge caused by huge resorption.